Analisis Insentif Perpajakan Terhadap Realisasi Penerimaan Perpajakan Tahun 2020 - Dani Andrean Widodo; Ni Ketut Millenia Krisnayanie (Jurnal Pacta Sunt Servanda, 2021)
The growth in the tax revenue component at the end of March 2020 was still sourced from taxes on household consumption, although tax revenues also still depended on the pressure from the weakening trend in the manufacturing industry and international trade activity, as well as the weakening economic activity of the spread of Covid-19. In line with the existence of regulations related to Work From Home (WFH) for both the government and private sectors, a slowdown in business activities began at the end of March 2020 which reduced the handover of the country which would then enter Domestic Value Added Tax (PPN DN) revenue in the month April 2020. This condition is likely to continue and contract even more in May, considering that in April some regions had implemented Large-Scale Social Restrictions (PSBB) in several affected areas. As the going in Indonesia, tax revenue in the first quarter of 2020 was recorded to have contracted or minus up to 2.5%. Several tax instruments after being used for handling Covid-19 are Corporate Income Tax and Import Tax (PDRI) consisting of several types, namely Income Tax (PPh) Article 22 imports, PPh Article 22 Exports, Import Value Added Tax (PPN), and Luxury Goods Sales Tax (PPnBM). The Minister of Finance issued Regulation of the Minister of Finance Number 23 of 2020 (PMK 23 of 2020) Regarding Tax Incentives for Taxpayers Affected by the Covid-19 Virus Outbreak. The provision of this incentive is a response from the government to the decline in productivity of business actors due to the economic decline of taxpayers due to this epidemic. This study aims to analyze the tax incentive tax on the realization of tax revenue in 2020 whether it is relevant and can help people ease the economic burden built by the spread of Covid-19 in Indonesia.